Behavioral portfolio theory - Wirasmi Wardhani (FORUM EKONOMI, 2016)
Mean-Variance Portfolio Theory (MVT) by Markowitz (1952) is a theory that most investor used when they are creating portfolio despite the unanswered issues that theory still can’t answer. One of which is how the investor can create a portfolio if the investor have many actions regarding the risks. The unsolved matters in MVT frame can be answered/solved through Behavioral Portfolio Theory (BPT). BPT explains how investor can create an optimal portfolio if the investor have many actions towards the risks. BPT also explains the investor is not always risk averse (the attitude that is always assumed in MVT). BPT furthermore explains the investor did not take their whole porftolio into consideration, in the contrary, the investor consider their portfolio as a collection from mental accounting (MA) subportfolio whereas each subportfolio is connected to a purpose dan every purpose has a threshold level.Keyword: Mean-variance portfolio theory, behavioral portfolio theory, mental accounting, behavioral finance